The Participation of Fishermen's Wives in Increasing Economic Income (Study of Four Families in Lasusua, North Kolaka Regency) - Mrs. Misbawati (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2022)
Fulfilling the economic needs of fishermen's families, in reality, is not only the full responsibility of the husband's role as the head of the family. However, in the economic activities of fishermen, the role of this person is also very important, especially in the aspect of marketing the caught fish. This paper examines the forms of participation carried out by fishermen's wives in Lasusua District, North Kolaka Regency. The results showed that the fishermen in this area succeeded in increasing the family's economic income, since they switched professions from garden workers to fishermen. The experience of pursuing a profession as a fisherman from the area of ​​origin, namely the Selayar Islands, allows them to exist working as fishermen and become suppliers of fish needs for local communities in this area. The focus of the study in this paper is limited to case studies of four families with different characteristics.